The effect of physico-chemically immobilized methylene blue and neutral red on the anode of microbial fuel cell - Popov, Arseniy L., University of Glamorgan, Pontypridd, Mid-Glamorgan, UK; Kim, J.R., University of Glamorgan, Pontypridd, Mid-Glamorgan, UK; Dinsdale, Richard M., University of Glamorgan, Pontypridd, Mid-Glamorgan, UK; Esteves, Sandra R., University of Glamorgan, Pontypridd, Mid-Glamorgan, UK; Guwy, Alan J., University of Glamorgan, Pontypridd, Mid-Glamorgan, UK; Premier, Giuliano C., University of Glamorgan, Pontypridd, Mid-Glamorgan, UK (Biotechnology and bioprocess engineering, 2012)
A fast and cost effective immobilization of electron carriers, methylene blue (MB) and neutral red (NR) by pH shift was proposed to improve bioanodic performance. The adsorption of mediators onto the carbon cloth anode was verified using cyclic voltammogram (CV) and the effect of the immobilized mediators on acclimation, power density, and acetate removal of MFCs was investigated. A peak power density of P∧max(MB) = 11.3 W/㎥ was achieved over days 110~120, as compared to P∧max(Control) = 5.4 W/㎥ and P∧max(NR) = 3.1 W/㎥ for the treated anode after 15 sequential fed-batch operations. The VFA removal rates however were similar for all MFC systems, ranging from 82 to 87%. It could be suggested that the increase in power density for the MB treated electrode resulted from an enhanced electron transport from exo-electrogenic bacteria. MB may also have a selective effect on the bacterial community during the start-up stage, increasing the voltage production and acetate removal from day 1 to 16. However, MFC with NR treated anode produced an initial voltage under 100 mV, with lower coulombic efficiency (CE). NR exhibited less favourable mediator molecule binding to the electrode surface, when subject to pH driven physico-chemical immobilization.